Promising clinical effect of arthroscopic autologous iliac bone grafting with suture anchor binding fixation for recurrent anterior shoulder instability - Tang, Bo; Zhao, Peng; Wu, Ping Shi; Fan, Cheng (Frontiers in Surgery, 2024)
BackgroundTo evaluate the clinical efficacy of arthroscopic autologous iliac bone grafting with suture anchor binding fixation combined with a Bankart repair for recurrent anterior shoulder dislocation with a significant anterior glenoid defect.MethodsPatients with recurrent anterior shoulder dislocation with an anterior glenoid defect area greater than 20% admitted to our department from March 2019 to March 2022 were prospectively enrolled. Arthroscopic autologous iliac bone grafting with suture anchor binding fixation combined with a Bankart repair was performed. Computed tomography (CT) images were captured preoperatively, immediately after surgery, and at 3, 6, and 12 months postoperatively to evaluate the glenoid defect area, graft area, and graft healing. Shoulder function was assessed using the Instability Severity Index, Oxford Shoulder Instability, and Rowe scores recorded preoperatively and at the final follow-up. The shoulder range of motion, shoulder stability test, surgery-related complications, subluxation/dislocation, and revision surgery were also evaluated.ResultsA total of 32 patients were included in the study, with an average follow-up time of 18.3 ± 6.3 months, when the graft healing rate was shown to be 100%. The area ratio of the graft to the glenoid was 37.6% ± 10.5% (range, 23.5%–44.1%) determined by an enface-view three-dimensional CT performed immediately after surgery, and 29.2 ± 8.2% (range, 19.6%–38.7%) at 12 months postoperatively. At the final follow-up, the glenoid defect had improved from 28.7 ± 6.4% (range, 20.5%–40.6%) before surgery to −10.2 ± 4.7% (range, −13.8% to 6.1%). The preoperative Rowe and Oxford scores were 56.4 ± 8.5 and 34.7 ± 7.1 respectively, which improved to 94.3 ± 6.7 and 15.3 ± 3.2 at the final follow-up (p < .001). All patients had no limited shoulder joint activity, no re-dislocation or revision surgery, and no neurovascular injury.ConclusionsFor recurrent anterior shoulder dislocation with an anterior glenoid defect area greater than 20%, arthroscopic autologous iliac bone grafting with suture anchor fixation combined with a Bankart repair produced a promising clinical effect. A significant shoulder function score was achieved, as was a 100% bone healing rate and ideal glenoid reconstruction without major complications. Thus, this technique may be considered an alternative to the classic Latarjet approach to treat recurrent anterior shoulder dislocation with an anterior glenoid defect area greater than 20%.Level of EvidenceIV.